Mitigating soil compaction and enhancing corn (Zea mays L.) growth through biological and non-biological amendments - Shahrzad Hejazi Mahabadi; Mahdi Shorafa; Babak Motesharezadeh; Hassan Etesami (BMC Plant Biology)
Abstract Soil compaction is a pressing issue in agriculture that significantly hinders plant growth and soil health, necessitating effective strategies for mitigation. This study examined the effects of sugarcane bagasse, both in its raw form and as biochar, along with biological activators (Bacillus simplex UTT1 and Phanerochaete chrysosporium) on soil characteristics and corn (Zea mays L.) plant biomass in a compacted soil. Using a completely randomized factorial design, we assessed their impact on soil bulk density, porosity, nutrient concentrations, and plant growth parameters. Results indicated that combining organic amendments with microbial inoculation (B. simplex UTT1 + P. chrysosporium) significantly reduced soil bulk density (7–14%) (p < 0.05) and enhanced soil aggregate stability (38%), soil permeability coefficient (52%), and total porosity (40%) (p < 0.01) compared to controls. Notably, the application of biochar and microbial inoculants improved soil moisture retention (p < 0.05) and soil nutrient availability, particularly potassium and phosphorus, which increased by 18% and 23%, respectively. Plant biomass responses (10–35%) varied, with combined microbial treatments (B. simplex UTT1 + P. chrysosporium) yielding optimal outcomes (p < 0.01) compared to individual applications. The study emphasizes that integrating organic amendments with biological processes not only mitigates soil compaction but also fosters soil health and productivity. These findings support the need for sustainable agricultural practices, highlighting the role of effective resource management in enhancing soil structure and crop yields. Future research should focus on understanding the underlying mechanisms of these interactions and their long-term implications for soil health and agricultural sustainability. Clinical trial number Not applicable.